DESAIN INOVASI PEMBELAJARAN DARING UNTUK MAHASISWA TUNANETRA MELALUI MODEL PEMBELAJARAN DISCOVERY LEARNING BERBASIS AUDIO DI PRODI PENDIDIKAN BAHASA DAN SASTRA INDONESIA UNIVERSITAS ISLAM MAKASSAR - Erwin Nurdiansyah; Supriadi; Jumriati; Abu Bakar Tumpu (AIJER: Algazali International Journal Of Educational Research, 2020)
Abstract: Development of audio-based discovery learning learning models in supporting the learning of children with special needs in listening and speaking learning as well as creating a learning environment that can encourage students with special needs to construct knowledge and skills personally. The method of implementing this activity uses the workshop method. The location for this activity is the Indonesian Language and Literature Education Study Program, Faculty of Teacher Training and Education, Makassar Islamic University. The subjects in this activity were lecturers and students of the Indonesian Language and Literature Education Study Program, Faculty of Teacher Training and Education, Makassar Islamic University. The implementation time of this activity is three months in 2021 or in odd semesters in the 2020-2021 school year. The implementation of this activity does not require a long time allocation because it is only a workshop. The results obtained from this workshop are, 1) developing audio-based discovery learning learning model RPS for students with disabilities, especially students with visual impairments; 2) Has developed audio-based teaching materials for students with disabilities, especially students with visual impairments; 3) Has developed audio-based learning media for students with disabilities, especially students with visual impairments; 4) Has developed an audio-based learning evaluation report for students with disabilities, especially students with visual impairments.